2023
DOI: 10.1177/09540083231181926
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 4-pyridine-bridge polybenzimidazolefor proton exchange membranes

Abstract: A series of polybenzimidazoles (PBIs) incorporated main chain 4-pyridine bridge groups were synthesized from 4,4′-([4,4′-bipyridine]-2,6,-diyl)bis (benzene-1,2-diamine) which reacted with four different diacids like isophthalic acid,4,4′-Oxibis benzoic acid, 5-amino isophthalic acid and 2,5-pyridine dicarboxylic acid using polyphosphoric acid as solvent. A process termed dispersion polymerizationhas been developed to prepare PBIs.For the membranepreparation, 4-pyridine-bridge polybenzimidazole (Py-PBI) product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…An optimum water uptake is necessary to obtain a PEM with both desirable mechanical stability and proton conductivity. 33 Water absorption by 2-Py-PBIs:PVPA membranes with various diacid monomers are hygroscopic polymers and have a great preference for forming intermolecular interactions with water molecules. After immersing the membranes in distilled water for 4 h at different temperatures, It has been observed that the quantity of water absorption in the 221I, 224P, 225A, and 22AO membranes at 35°C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An optimum water uptake is necessary to obtain a PEM with both desirable mechanical stability and proton conductivity. 33 Water absorption by 2-Py-PBIs:PVPA membranes with various diacid monomers are hygroscopic polymers and have a great preference for forming intermolecular interactions with water molecules. After immersing the membranes in distilled water for 4 h at different temperatures, It has been observed that the quantity of water absorption in the 221I, 224P, 225A, and 22AO membranes at 35°C.…”
Section: Resultsmentioning
confidence: 99%
“…A programmable temperature controller with ramp and soak functions was used to regulate the reaction temperature (Scheme 1). 33
Scheme 1.Polymer Synthesis: Derivatives of 2-Py-PBIs polymers were synthesized from derivative of 2-Py-TAB monomer with various dicarboxylic acids by dispersion polymerization. The polymer are abbreviated as 2-Py-PBI-Ar, where ‘Ar’ indicates the DCA used in the polymerization.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations